The impact of using measurement software in the quantity surveying consultancy - Lim, Meow Ying (2020)
A quantity surveyor is a professional that work in the construction industry concerned with construction cost. The purpose of this research is to investigate the impact of measurement software to the quantity surveying consultancy. The objectives of this research are (i) to identify measurement software undertaken by quantity surveying consultant firms, (ii) to determine the benefits of using measurement software and (iii) to identify the negative impacts of using measurement software. Measurement software as a tool that helps quantity surveyors to do measurement and automatically quantification items that measured for BQ preparation in a short period time and improve the efficiency of the projects in estimating. Quantitative method approach was adopted in this research. A set of questionnaire was distributed to 138 quantity surveyors related personnel who work in consultant firms to identify software that undertakes by the firm and evaluate the relative importance on the impact of measurement software. From this research, Cubicost is the most commonly used measurement software. The finding showed that the highest 3 benefits of measurement impacts are “It can store data and information”, “Can reduce measurement workload” and “Reduce measurement mistake”. However, it has highest 3 negative impacts brought to quantity surveyors such as “It is cost wasting because it has high installation cost”, “Quantity surveyors become more rely on it” and “Reduce number of employment”. Mann-Whitney U test was conducted and the results revealed that there was a significant difference in the benefit of measurement software which was “Can store data and information” across gender. Moreover, Kruskal-Wallis test was conducted and the results showed that there was a significant difference in benefit and negative impacts of using measurement software across a different group of age and working experience such as “Improve cooperation and communication among quantity surveyors”, “Attend measurement software training is wasting of time”, “The implementation of measurement software will reduce number of employment” and “Able to do measurement without using measurement software”. This research is helpful to the quantity surveying consultancy to gain the benefits of using measurement software so it will bring benefit to the construction industry.